Effectiveness Between Mango Honey and Kesambi Honey As Antibacterial Against Streptococcus Pyogenes - Borromeu, Salvador BHWD; Isbandiati, Endang; Pramono, Adi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Infectious disease is one of the biggest health problems in developing countries, including Indonesia. The development of the discovery of antibiotics was not balanced with the development of resistance that occurred after that Group A streptococcus β hemolytic causes various events of a severe degree of infection. Now many people use natural ingredients as an alternative to antibiotics, one of which is honey. Aim: Knowing the benefits of mango honey and kesambi honey as an antibacterial against Streptococcus pyogenes and knowing the difference in the effectiveness and potency to inhibit growth and kill Streptococcus pyogenes between the two honey. Method: Using the macro dilution method in determining the value of MIC and the streaking method to determine the value of MBC. Results: MIC mango honey at 15.625 µL, MIC kesambi honey at 15.625 µL, MBC mango honey at 15.625 µL, and MBC kesambi honey at 31.25 µL. Conclusion: There is a difference of MBC between mango honey and kesambi honey against Streptococcus pyogenes where mango honey at 15.625 µL and kesambi honey at 31.25 µL, there is no difference in MIC between mango honey and kesambi honey, and the effectiveness and potency of mango honey as an antibacterial against Sp higher than kesambi honey which was observed through differences in the value of MBC.